PENGOLAHAN JADWAL SIDANG PENGADILAN AGAMA DENGAN SMS GATEWAY (STUDI KASUS PENGADILAN AGAMA BANTUL) - Danisworo, Nugroho; Fatkhiyah, Erfanti (Jurnal Script, 2014)
ABSTRACTServices SMS (Short messange Service) should be familiar to most of the general public as a service to deliver a short message. Beside cheapest, practice, and easy to use, SMS (Short Messenger Service) features is always present in all types of mobile phones.Court of religion as a state institution in charge of the various cases that are not small, so it takes the court schedule processing system based on SMS Gateway to facilitate litigants to access court schedule information. Expanded of court schedule processing applications using the programming language PHP, MySQL data storage and Gammu as SMS gateway engine. This system has a SMS Gateway service that will provide automated reply after the user sending the SMS service with the specified format in the system. Sms gateway service system is useful to the litigants in religious courts and provide court schedule information... . Keywords: Processing court schedule, SMS (Short messange Service), SMS Gateway